The Slavic genitive singular as the subject of participles in –no- and –to- - William R. Schmalstieg (Linguistica, 1976)
Hirt, 1934, 119, notes the use of the genitive case in Indo-European as the sub ject of a passive participle and gives the examples Greek 'von Gott gegeben', poetic 'erschlagen von Ai', Sanskrit patjuh krītā 'vom Gatten gekauft', tā asja prājah srštāh 'die von ihm geschaffenen Wesen' . The use of the genitive case as the subject of the Lithuanian -t- participles is well known. Cf. , e.g. , Tà knygà bùvo brólio pérskaityta ' the book was read (through) by the brother'.